Hubungan harga diri dengan tingkat kesepian pada lansia di LKS LU Pangesti Lawang - Yulianda, Eva (JOURNAL OF Mental Health Concerns, 2024)
Abstract Background: Self-esteem is a risk factor for psychosocial problems in the elderly that cause low self-esteem.Low self-esteem occurs due to the loss of social status, power, role in life, work and results in the elderly feelinguseless, helpless, feeling guilty, feeling hopeless which then causes psychological problems in the form ofloneliness.Purpose: To identifying the relationship between self-esteem and the level of loneliness of the elderly in LKS LUPangesti Lawang.Method: The study uses a correlational descriptive method with a cross sectional approach. The researchsample was 30 elderly respondents who had been selected using the purposive sampling technique. Datacollection was carried out through filling out questionnaires, and data analysis was carried out univariate andbivariate with the Spearman correlation test through the SPSS 25 program.Results: The results of the study showed that out of 30 respondents, 64.3% (18 elderly) experienced low selfesteemand 60.0% (18 elderly) experienced moderate loneliness. The results of the statistical test obtained avalue of p = 0.00 < 0.05.Conclution: There is a relationship between self-esteem and the level of loneliness in the elderly, as evidencedby the significance value of p-value = 0.00 where p < 0.05, which means there is a relationship between selfesteemand the level of loneliness in the elderly.